The importance of stimulation of metabolism processes in the body of Ovis aries L. by biophysical methods - Rajamuradov Zaynitdin; Rakhmatova Nigora; Turamkulov Shokir; Khaydarov Siroj; Rajamuradova Nuriniso; Normuhammedova Feruza (BIO Web of Conferences)
In this article, for the first time in the extreme conditions of Uzbekistan, in order to reduce farm costs from born male lambs, data on the use of low-frequency laser radiation as one of the biophysical methods is presented and summarized, which, as studies have shown, ensures the normal course of physiological processes in the body of male lambs that fall into a state of stress after separation from their mothers and the cessation of breastfeeding. The work presents reliable data on the positive effect of this method, which also improved the quality indicators of the resulting livestock products.